2022
DOI: 10.3390/catal12050566
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deoxygenation of Sludge Palm Oil into Diesel Range Fuel over Mn-Mo Supported on Activated Carbon Catalyst

Abstract: Originating from deoxygenation (DO) technology, green diesel was innovated in order to act as a substitute for biodiesel, which contains unstable fatty acid alkyl ester owing to the existence of oxygenated species. Green diesel was manufactured following a process of catalytic DO of sludge palm oil (SPO). An engineered Mn(0.5%)-Mo(0.5%)/AC catalyst was employed in a hydrogen-free atmosphere. The influence of Manganese (Mn) species (0.1–1 wt.%) on DO reactivity and the dissemination of the product were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A diffractometer (Shimadzu, model XRD 6000, Duisburg, Germany) was used to perform XRD and to establish the catalyst's crystalline profile. Debye-Scherrer's formula was used to compute the specimens' crystallite size D (D = β hkl × 0.9 × 1.5438/Cos (θ)) [60]. A temperature-programmed desorption (TPD) technique (ThermoScientific TPDRO 1100, Waltham, MA, USA) was used to ascertain the active site density and the catalyst acid strength; the probe molecule employed was A reactor equipped with a thermal conductivity detector was used for the experiment, into which 0.07 g catalyst was inserted and then subjected to a temperature of 150 • C for 45 min.…”
Section: Catalyst Characterisationmentioning
confidence: 99%
“…A diffractometer (Shimadzu, model XRD 6000, Duisburg, Germany) was used to perform XRD and to establish the catalyst's crystalline profile. Debye-Scherrer's formula was used to compute the specimens' crystallite size D (D = β hkl × 0.9 × 1.5438/Cos (θ)) [60]. A temperature-programmed desorption (TPD) technique (ThermoScientific TPDRO 1100, Waltham, MA, USA) was used to ascertain the active site density and the catalyst acid strength; the probe molecule employed was A reactor equipped with a thermal conductivity detector was used for the experiment, into which 0.07 g catalyst was inserted and then subjected to a temperature of 150 • C for 45 min.…”
Section: Catalyst Characterisationmentioning
confidence: 99%
“…Consequently, this approach significantly enhances the cycling efficiency of the electrodes. [16][17][18][19][20][21] Furthermore, it has been found that the synergic effects of adsorption and electrocatalytic capabilities significantly impede the dissolution of polysulfides and effectively reduce the shuttle effect. 22 There is a growing consensus that layered double hydroxides (LDHs) are the promising choice for this purpose.…”
Section: Introductionmentioning
confidence: 99%